Method for improving corrosion resistance of magnesium alloy

By forming a silane composite passivation layer and hardening layer on the surface of the magnesium alloy, the problem of insufficient corrosion resistance of magnesium alloy is solved, and its corrosion resistance and hardness properties are significantly improved, ensuring the stability and service life of magnesium alloy.

CN119177438AInactive Publication Date: 2024-12-24FUGU COUNTY YONGHUA IND & TRADE CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411691474.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-25
Publication Date
2024-12-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The corrosion resistance of existing magnesium alloys is insufficient, and the surface coating is prone to falling off and aging, which affects the performance of use.

Method used

The film forming liquid is used to form a silane composite passivation layer on the surface of the magnesium alloy, and the surface pore structure and crosslink density are optimized through pretreatment and heating treatment of the immersion liquid and cover to form a dense passivation layer, while using two trioxide. Iron powder, nickel oxide powder, calcium fluoride powder and silica powder are used as covers to form a hardened layer.

Benefits of technology

It significantly improves the corrosion resistance and hardness of magnesium alloys, ensures the stability and density of the coating, and extends the service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119177438A_ABST
    Figure CN119177438A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of magnesium alloys, in particular to a method for improving the corrosion resistance of a magnesium alloy. The method comprises the following steps that the surface of a magnesium alloy plate is polished with abrasive paper to remove burrs, a soaking solution is prepared, the magnesium alloy plate is put into the soaking solution to be soaked, and a covering material is prepared; the method comprises the following steps: preparing a magnesium alloy plate, coating the surface of the magnesium alloy plate with a covering material, carrying out micro-forging hammering treatment on the surface of the magnesium alloy plate to prepare a film forming solution, putting the magnesium alloy plate subjected to micro-forging hammering into the film forming solution for treatment, hanging the magnesium alloy plate in a drying oven, carrying out heat preservation at 220-230 DEG C for 15-20 minutes, taking out the magnesium alloy plate, and putting the magnesium alloy plate at normal temperature for 12 hours to finish treatment, the film forming performance of the silane composite passivation layer can be optimized, the passivation layer wraps a gelatinization layer formed by soaking liquid, the crosslinking density of silane in the passivation layer is effectively improved, and therefore the compactness of the passivation layer is improved, and the corrosion resistance of the magnesium alloy is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of magnesium alloys, and in particular to a method for improving the corrosion resistance of magnesium alloys. Background Art

[0002] Magnesium alloy is an alloy composed of magnesium and other elements. The magnesium alloy industry has broad market prospects. Magnesium alloy is widely used in aviation, aerospace, defense industry, automobile industry and in the production of various magnesium alloy materials.

[0003] In the prior art, magnesium alloys are usually coated with a surface coating to improve the corrosion resistance of magnesium alloys. During the use of magnesium alloys, it is easy for the coating to fall off and age, resulting in the corrosion resistance of the water-based coating being less than ideal, thus affecting the performance of the magnesium alloy. Based on this, the present invention provides a method for improving the corrosion resistance of magnesium alloys. Summary of the invention

[0004] The purpose of the present invention is to provide a method for improving the corrosion resistance of magnesium alloys. The magnesium alloy prepared by the present invention not only has good corrosion resistance, but also has excellent hardness performance, which effectively improves the performance of the magnesium alloy.

[0005] To achieve the above object, the present invention provides the following technical solutions: A method for improving the corrosion resistance of a magnesium alloy comprises the following steps: S1: selecting a magnesium alloy plate, and grinding the surface of the magnesium alloy plate with sandpaper to remove burrs; S2: preparing an immersion solution, and immersing the magnesium alloy plate in the immersion solution; S3: preparing a covering material, and coating the surface of the magnesium alloy plate with the covering material, and sending the coated magnesium alloy plate into an oven, and drying it at 220°C to 240°C for 3 h to 5 h; S4: performing a micro-forging hammering treatment on the surface of the magnesium alloy plate; S5: preparing a film-forming liquid, and placing the magnesium alloy plate after the micro-forging hammering into the film-forming liquid for treatment; S6: hanging the magnesium alloy plate in an oven, keeping it warm at 220°C to 230°C for 15 to 20 min, and taking it out and placing it at room temperature for 12 h to complete the treatment.

[0006] Among them, the preparation of the film-forming liquid includes: S511. Adding aminopropyltriethoxysilane to water, mixing and stirring for 10 to 15 minutes, and then adding ammonia water to adjust the pH value to 7 to obtain a first prepared liquid; S512. Adding propyltrimethoxysilane to the first prepared liquid, heating to 80 to 90°C, keeping warm for 50 to 60 minutes, stirring slowly during the insulation process, adding vanadyl sulfate after cooling to room temperature, and then adding ammonia water to adjust the pH value to 6.5 to obtain a second prepared liquid; S513. Adding a dispersant to the second prepared liquid, mixing evenly to obtain a third prepared liquid, stirring the third prepared liquid continuously for 5 to 8 minutes, filtering with a 200-mesh filter cloth to obtain a film-forming liquid.

[0007] The magnesium alloy plate is placed in the film-forming liquid for treatment, including: S521. Immersing the magnesium alloy plate in the film-forming liquid for 4 to 6 minutes, and continuously stirring the film-forming liquid during the immersion process; S522. Slowly taking out the magnesium alloy plate and letting it stand for 2 to 3 minutes; S523. Repeating S521 and S522 in sequence for 4 to 6 times.

[0008] Furthermore, in S511, when the aminopropyltriethoxysilane is added to the water, the mass ratio of the water to the aminopropyltriethoxysilane is 1:(0.1-0.2).

[0009] Further, in S512: when the propyltrimethoxysilane is added to the first formulated liquid, the mass of the added propyltrimethoxysilane accounts for 25-30% of the mass of the first formulated liquid; When the vanadyl sulfate is added to the first prepared liquid, the mass of the added vanadyl sulfate accounts for 10-15% of the mass of the first prepared liquid.

[0010] Furthermore, in S513, when the dispersant is added to the second prepared liquid, the mass of the added dispersant accounts for 4-6% of the mass of the second prepared liquid.

[0011] Furthermore, the dispersant is selected from any one of alkyl sulfate, alkyl sulfonate and sodium pyrophosphate.

[0012] Furthermore, in S2, preparing the soaking liquid includes: adding corn starch to water in a mass ratio of 1:(3-4), stirring and mixing for standby use, and continuing to stir evenly during use and soaking.

[0013] Furthermore, in S3, the preparation of the covering material includes: S31. Weigh 10 to 12 parts of ferric oxide powder, 8 to 10 parts of nickel oxide powder, 6 to 8 parts of calcium fluoride powder and 4 to 6 parts of silicon dioxide powder, put all of them into a mixer to mix, and obtain a mixture; S32. Add a mixed liquid with a mass that is 1.4 to 1.6 times the mass of the mixture to the mixture, and obtain a slurry after mixing; S33. Send the slurry into a magnetic stirrer, stir it at a speed of 600 to 800 r / min for 40 to 50 minutes, and obtain the covering material.

[0014] Furthermore, in S31, the particle sizes of the ferric oxide powder, the nickel oxide powder, the calcium fluoride powder and the silicon dioxide powder are all less than or equal to 20 μm.

[0015] Furthermore, before adding a mixed liquid having a mass that is 1.4 to 1.6 times the mass of the mixed material to the mixed material, the step S32 further includes: mixing propylene glycol and anhydrous ethanol in a mass ratio of 1:(0.4 to 0.6) to obtain the mixed liquid.

[0016] Furthermore, in S4, micro-forging hammering treatment is performed on the surface of the magnesium alloy plate, including: placing the magnesium alloy plate on a hammering device; the diameter of the micro-forging head of the hammering device is 3-5 mm, the stroke is 1.5-2 mm, the impact frequency is 100 Hz, the step amount is 0.1 mm, and the feed speed is 600-800 mm / min; controlling the micro-forging head to hammer the magnesium alloy plate.

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention forms a silane composite passivation layer on the surface of a magnesium alloy plate by a film-forming liquid, and the passivation layer plays a role of corrosion protection on the surface of the magnesium alloy. At the same time, the magnesium alloy plate is pre-treated by an immersion liquid and a covering material. After the magnesium alloy plate is subsequently heated, the carbohydrate in the immersion liquid is used as the main raw material, which can produce gelatinization when heated and produce a cross-linking reaction with the magnesium alloy plate, the covering material and the film-forming liquid, so as to optimize the surface pore structure of the plate, thereby optimizing the film-forming performance of the silane composite passivation layer. The passivation layer wraps the gelatinization layer formed by the immersion liquid inside, effectively improving the cross-linking density of silane in the passivation layer, thereby improving the compactness of the passivation layer, and further improving the corrosion resistance of the magnesium alloy.

[0018] 2. The present invention coats ferric oxide powder, nickel oxide powder, calcium fluoride powder and silicon dioxide powder as covering materials on the surface of the magnesium alloy plate. After the metal powder is prepared into a slurry, it is evenly filled between the gelatinized carbon water and the passivation layer, and after drying and heating treatment, it hardens to form a solidified layer, which plays a role in improving the surface hardness of the magnesium alloy plate. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 The invention proposes a flow chart of a method for improving the corrosion resistance of magnesium alloy. DETAILED DESCRIPTION

[0020] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0021] In order to enable those skilled in the art to better understand the solution of the present application, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the accompanying drawings.

[0022] This embodiment provides a method for improving the corrosion resistance of magnesium alloy, comprising the following steps: S1: Select a magnesium alloy plate and use sandpaper to grind the surface of the magnesium alloy plate to remove burrs.

[0023] S2: preparing a soaking liquid, and placing the magnesium alloy sheet into the soaking liquid for soaking.

[0024] S3: preparing a covering material, and coating the surface of the magnesium alloy sheet with the covering material, sending the coated magnesium alloy sheet into an oven, and drying it at 220° C. to 240° C. for 3 h to 5 h.

[0025] S4: Micro-forging and hammering treatment is performed on the surface of the magnesium alloy sheet.

[0026] S5: preparing a film-forming liquid, and placing the magnesium alloy sheet after micro-forging and hammering into the film-forming liquid for treatment.

[0027] Among them, the preparation of the film-forming liquid includes: S511. Adding aminopropyltriethoxysilane to water, mixing and stirring for 10 to 15 minutes, and then adding ammonia water to adjust the pH value to 7 to obtain a first prepared liquid; S512. Adding propyltrimethoxysilane to the first prepared liquid, heating to 80 to 90°C, keeping warm for 50 to 60 minutes, stirring slowly during the insulation process, waiting to cool to room temperature and then adding vanadyl sulfate, and then adding ammonia water to adjust the pH value to 6.5 to obtain a second prepared liquid; S513. Adding a dispersant to the second prepared liquid, mixing evenly to obtain a third prepared liquid, stirring the third prepared liquid continuously for 5 to 8 minutes, filtering with a 200-mesh filter cloth to obtain a film-forming liquid.

[0028] The magnesium alloy plate is placed in the film-forming liquid for treatment, including: S521. The magnesium alloy plate is immersed in the film-forming liquid for 4 to 6 minutes, and the film-forming liquid is continuously stirred during the immersion process; S522. The magnesium alloy plate is slowly taken out and allowed to stand for 2 to 3 minutes; S523. S521 and S522 are repeated in sequence for 4 to 6 times.

[0029] S6: Hang the magnesium alloy sheet in an oven and keep it at 220°C to 230°C for 15 to 20 minutes. After taking it out, place it at room temperature for 12 hours to complete the treatment.

[0030] In this embodiment, the magnesium alloy plate is pre-soaked in the soaking liquid, the covering material is coated on the plate surface of the magnesium alloy plate, and the film-forming liquid is used to treat the titanium alloy plate multiple times, so that a layer of carbohydrate, a layer of covering material and a layer of uniform silane composite passivation layer can be formed on the surface of the magnesium alloy plate in sequence. Afterwards, after the magnesium alloy plate is heated, the carbohydrate in the soaking liquid can be gelatinized and react with the magnesium alloy plate, the covering material and the film-forming liquid to optimize the surface pore structure of the plate, thereby optimizing the film-forming performance of the silane composite passivation layer. In addition, the passivation layer wraps the gelatinized layer formed by the soaking liquid inside, effectively improving the cross-linking density of silane in the passivation layer, thereby improving the compactness of the passivation layer and the corrosion resistance of the magnesium alloy.

[0031] In some embodiments, in S511, when aminopropyltriethoxysilane is added to water, the mass ratio of water to aminopropyltriethoxysilane is 1:(0.1-0.2).

[0032] In this embodiment, the magnesium alloy plate is immersed and removed multiple times so that the film-forming liquid can be evenly covered on the surface of the magnesium alloy plate. After the magnesium alloy plate is subjected to high-temperature treatment in an oven, the film-forming liquid forms a crust on the surface of the magnesium alloy plate to form a solidified layer.

[0033] In some embodiments, in S512: when propyltrimethoxysilane is added to the first formulated liquid, the mass of the added propyltrimethoxysilane accounts for 25-30% of the mass of the first formulated liquid; When adding vanadyl sulfate to the first prepared liquid, the mass of the added vanadyl sulfate accounts for 10-15% of the mass of the first prepared liquid.

[0034] In some embodiments, in S513, when adding a dispersant to the second prepared liquid, the mass of the added dispersant accounts for 4-6% of the mass of the second prepared liquid.

[0035] In some embodiments, the dispersant is selected from any one of alkyl sulfate, alkyl sulfonate and sodium pyrophosphate.

[0036] In some embodiments, in S2, preparing the soaking liquid includes: adding corn starch to water in a mass ratio of 1: (3-4), stirring and mixing for standby use, and continuing to stir evenly during use and soaking.

[0037] In this embodiment, carbohydrates in the soaking liquid are used as the main raw material, which can produce gelatinization when heated and produce cross-linking reactions with the magnesium alloy plate, covering material and film-forming liquid, so as to optimize the surface pore structure of the plate, thereby optimizing the film-forming performance of the silane composite passivation layer. The passivation layer wraps the gelatinization layer formed by the soaking liquid inside, effectively improving the cross-linking density of silane in the passivation layer, thereby improving the density of the passivation layer, and then improving the corrosion resistance of the magnesium alloy.

[0038] In some embodiments, in S3, the preparation of the covering material includes: S31. Weigh 10 to 12 parts of ferric oxide powder, 8 to 10 parts of nickel oxide powder, 6 to 8 parts of calcium fluoride powder and 4 to 6 parts of silicon dioxide powder, put all of them into a mixer to mix, and obtain a mixture; S32. Add a mixed liquid with a mass 1.4 to 1.6 times the mass of the mixture to the mixture, and obtain a slurry after mixing; S33. Send the slurry into a magnetic stirrer and stir it at a speed of 600 to 800 r / min for 40 to 50 minutes to obtain the covering material.

[0039] In this embodiment, the slurry is made by mixing metal powders. The slurry has more solids and therefore has poor fluidity. The slurry covers the surface of the magnesium alloy plate more firmly.

[0040] In some embodiments, in S31 , the particle sizes of the ferric oxide powder, the nickel oxide powder, the calcium fluoride powder, and the silicon dioxide powder are all less than or equal to 20 μm.

[0041] In this embodiment, after being covered on the surface of the magnesium alloy plate, the relatively fine-grained ferric oxide powder, nickel oxide powder, calcium fluoride powder and silicon dioxide powder can form a rich pore structure on the surface of the magnesium alloy plate, facilitating the effective combination of the covering material and the film-forming liquid.

[0042] In some embodiments, before adding a mixed liquid having a mass that is 1.4 to 1.6 times the mass of the mixed material to the mixed material, S32 further includes: mixing propylene glycol and anhydrous ethanol in a mass ratio of 1: (0.4 to 0.6) to obtain a mixed liquid.

[0043] In some embodiments, in S4, micro-forging and hammering treatment of the surface of the magnesium alloy plate includes: placing the magnesium alloy plate on a hammering device; the diameter of the micro-forging head of the hammering device is 3 to 5 mm, the stroke is 1.5 to 2 mm, the impact frequency is 100 Hz, the step amount is 0.1 mm, and the feed speed is 600 to 800 mm / min; controlling the micro-forging head to hammer the magnesium alloy plate.

[0044] In this embodiment, by micro-forging and hammering treatment on the surface of the magnesium alloy plate, the surface of the magnesium alloy plate is subjected to high-frequency single-point impact force during the treatment process, so that the coating layer is closely combined with the magnesium alloy surface, thereby improving the stability of the coating structure.

[0045] Based on the above embodiments, the inventors also conducted the following experiments:

[0046] It should be noted that the raw materials used in the following experiments are all commercially available raw materials.

[0047] Experiment 1: A method for improving the corrosion resistance of a magnesium alloy comprises the following steps: Select a magnesium alloy plate, use sandpaper to grind the surface of the magnesium alloy plate to remove burrs, and put the magnesium alloy plate into the soaking liquid; The soaking liquid is prepared by the following method: corn starch is added into water in a mass ratio of 1:3, stirred and mixed and then set aside for use, and stirring is continued during use and soaking; After the magnesium alloy sheet is soaked, it is taken out, and the surface of the magnesium alloy sheet is coated with a covering material, and then the surface of the magnesium alloy sheet is subjected to micro-forging and hammering treatment; The covering material is composed of the following raw materials in parts by weight: 10 parts of ferric oxide powder, 8 parts of nickel oxide powder, 6 parts of calcium fluoride powder and 4 parts of silicon dioxide powder; The particle size of ferric oxide powder, nickel oxide powder, calcium fluoride powder and silicon dioxide powder is ≤20μm; The covering material is prepared by the following method: Step 1: Weigh the various raw materials of the covering material as needed, and then put them all into a mixer to mix, and obtain a mixed material for standby use; Step 2: Add a mixed liquid 1.4 times the mass of the mixed material, and mix to obtain a slurry; The mixed liquid is prepared by the following method: mixing glycerol and anhydrous ethanol, wherein the mass ratio of glycerol to anhydrous ethanol is 1:0.4, and mixing to obtain a mixed liquid; Step 3: Place the slurry into a magnetic stirrer and stir at 600 r / min for 40 min to obtain a covering material, which is then evenly applied to the surface of the magnesium alloy sheet; Step 4: Place the magnesium alloy sheet coated with the covering material into an oven, set the temperature at 220°C for drying, maintain the constant temperature in the oven for 3 hours, and take it out to complete the coating process; The micro-forging hammer treatment method is as follows: the micro-forging head diameter is 3 mm, the stroke is 1.5 mm, the impact frequency is 100 Hz, the step size is 0.1 mm, and the feed speed is 600 mm / min; Prepare the film-forming solution and set it aside for use after the preparation is completed; The film-forming solution is prepared by the following method: (1) adding aminopropyl triethoxysilane to water, mixing and stirring for 10 minutes, wherein the mass ratio of water to aminopropyl triethoxysilane is 1:0.1, and then adding ammonia water to adjust the pH value to 7 to obtain a first prepared solution for standby use; (2) adding propyltrimethoxysilane accounting for 25% of the mass of the first prepared liquid to the first prepared liquid, heating to 80° C., and keeping warm for 50 minutes. During the keeping warm process, stirring slowly continuously, and after cooling to room temperature, adding vanadyl sulfate accounting for 10% of the mass of the first prepared liquid, and adding ammonia water to adjust the pH value to 6.5, to obtain a second prepared liquid for standby use; (3) adding a dispersant accounting for 4% of the mass of the second prepared liquid to the second prepared liquid, mixing evenly to obtain a third prepared liquid, stirring the third prepared liquid continuously for 5 minutes, and filtering with a 200-mesh filter cloth to obtain a membrane-forming liquid; The dispersant is selected from any one of alkyl sulfate, alkyl sulfonate, and sodium pyrophosphate; The magnesium alloy sheet is placed in a film-forming liquid for treatment; The treatment method of the magnesium alloy plate and the film-forming liquid is as follows: immerse the magnesium alloy plate in the film-forming liquid for 4 minutes, continuously stir the film-forming liquid during the immersion process, slowly take out the magnesium alloy plate, let it stand for 2 minutes and continue to immerse it in the film-forming liquid for 4 minutes, repeat the immersion and taking out and standing operation 4 times, hang the magnesium alloy plate in an oven set at 220°C, keep warm for 15 minutes, take it out and place it at room temperature for 12 hours to complete the treatment.

[0048] Experiment 2: A method for improving the corrosion resistance of a magnesium alloy comprises the following steps: Select a magnesium alloy plate, use sandpaper to grind the surface of the magnesium alloy plate to remove burrs, and put the magnesium alloy plate into the soaking liquid; The soaking liquid is prepared by the following method: corn starch is added into water in a mass ratio of 1:3.5, stirred and mixed and then set aside for use, and stirring is continued during use and soaking; After the magnesium alloy sheet is soaked, it is taken out, and the surface of the magnesium alloy sheet is coated with a covering material, and then the surface of the magnesium alloy sheet is subjected to micro-forging and hammering treatment; The covering material is composed of the following raw materials in parts by weight: 11 parts of ferric oxide powder, 9 parts of nickel oxide powder, 7 parts of calcium fluoride powder and 5 parts of silicon dioxide powder; The particle size of ferric oxide powder, nickel oxide powder, calcium fluoride powder and silicon dioxide powder is ≤20μm; The covering material is prepared by the following method: Step 1: Weigh the various raw materials of the covering material as needed, and then put them all into a mixer to mix, and obtain a mixed material for standby use; Step 2: Add a mixed liquid 1.5 times the mass of the mixed material, and mix to obtain a slurry; The mixed liquid is prepared by the following method: propylene glycol and anhydrous ethanol are mixed, the mass ratio of propylene glycol to anhydrous ethanol is 1:0.5, and the mixed liquid is prepared; Step 3: Place the slurry into a magnetic stirrer and stir at 700 r / min for 45 min to obtain a covering material, which is then evenly applied to the surface of the magnesium alloy sheet; Step 4: Place the magnesium alloy sheet coated with the covering material into an oven, set the temperature at 230°C for drying, maintain the constant temperature in the oven for 4 hours, and then take it out to complete the coating process; The micro-forging hammer treatment method is as follows: the micro-forging head diameter is 4 mm, the stroke is 1.7 mm, the impact frequency is 100 Hz, the step size is 0.1 mm, and the feed speed is 700 mm / min; Prepare the film-forming solution and set it aside for use after the preparation is completed; The film-forming solution is prepared by the following method: (1) adding aminopropyl triethoxysilane to water, mixing and stirring for 12 minutes, wherein the mass ratio of water to aminopropyl triethoxysilane is 1:0.15, and then adding ammonia water to adjust the pH value to 7 to obtain a first prepared solution for standby use; (2) Add propyltrimethoxysilane accounting for 27% of the mass of the first prepared liquid to the first prepared liquid, heat to 85° C., and keep warm for 55 minutes. Stir slowly during the insulation process. After cooling to room temperature, add vanadyl sulfate accounting for 12% of the mass of the first prepared liquid, and add ammonia water to adjust the pH value to 6.5 to obtain a second prepared liquid for standby use; (3) adding a dispersant accounting for 5% of the mass of the second prepared liquid to the second prepared liquid, mixing evenly to obtain a third prepared liquid, stirring the third prepared liquid continuously for 6 minutes, and filtering with a 200-mesh filter cloth to obtain a membrane-forming liquid; The dispersant is selected from any one of alkyl sulfate, alkyl sulfonate, and sodium pyrophosphate; The magnesium alloy sheet is placed in a film-forming liquid for treatment; The treatment method of the magnesium alloy plate and the film-forming liquid is as follows: immerse the magnesium alloy plate in the film-forming liquid for 5 minutes, continuously stir the film-forming liquid during the immersion process, slowly take out the magnesium alloy plate, let it stand for 2.5 minutes, continue to immerse it in the film-forming liquid for 5 minutes, repeat the immersion and taking out and standing operation 5 times, hang the magnesium alloy plate in an oven set at 225°C, keep it warm for 17 minutes, take it out and place it at room temperature for 12 hours to complete the treatment.

[0049] Experiment 3: A method for improving the corrosion resistance of a magnesium alloy comprises the following steps: Select a magnesium alloy plate, use sandpaper to grind the surface of the magnesium alloy plate to remove burrs, and put the magnesium alloy plate into the soaking liquid; The soaking liquid is prepared by the following method: corn starch is added into water in a mass ratio of 1:4, stirred and mixed and then set aside for use, and stirring is continued during use and soaking; After the magnesium alloy sheet is soaked, it is taken out, and the surface of the magnesium alloy sheet is coated with a covering material, and then the surface of the magnesium alloy sheet is subjected to micro-forging and hammering treatment; The covering material is composed of the following raw materials in parts by weight: 12 parts of ferric oxide powder, 10 parts of nickel oxide powder, 8 parts of calcium fluoride powder and 6 parts of silicon dioxide powder; The particle size of ferric oxide powder, nickel oxide powder, calcium fluoride powder and silicon dioxide powder is ≤20μm; The covering material is prepared by the following method: Step 1: Weigh the various raw materials of the covering material as needed, and then put them all into a mixer to mix, and obtain a mixed material for standby use; Step 2: Add a mixed liquid 1.6 times the mass of the mixed material, and mix to obtain a slurry; The mixed liquid is prepared by the following method: propylene glycol and anhydrous ethanol are mixed, the mass ratio of propylene glycol to anhydrous ethanol is 1:0.6, and the mixed liquid is prepared; Step 3: Place the slurry into a magnetic stirrer and stir at 800 r / min for 50 min to obtain a covering material, which is then evenly applied to the surface of the magnesium alloy sheet; Step 4: Place the magnesium alloy sheet coated with the covering material into an oven, set the temperature to 240°C for drying, maintain the constant temperature in the oven for 5 hours, and complete the coating process after taking it out; The micro-forging hammer treatment method is as follows: the micro-forging head diameter is 5 mm, the stroke is 2 mm, the impact frequency is 100 Hz, the step size is 0.1 mm, and the feed speed is 800 mm / min; Prepare the film-forming solution and set it aside for use after the preparation is completed; The film-forming solution is prepared by the following method: (1) adding aminopropyl triethoxysilane to water, mixing and stirring for 15 minutes, wherein the mass ratio of water to aminopropyl triethoxysilane is 1:0.2, and then adding ammonia water to adjust the pH value to 7 to obtain a first prepared solution for standby use; (2) adding propyltrimethoxysilane accounting for 30% of the mass of the first prepared liquid to the first prepared liquid, heating to 90° C., and keeping warm for 60 minutes. During the keeping warm process, stirring slowly continuously, and after cooling to room temperature, adding vanadyl sulfate accounting for 15% of the mass of the first prepared liquid, and adding ammonia water to adjust the pH value to 6.5, to obtain a second prepared liquid for standby use; (3) adding a dispersant accounting for 6% of the mass of the second prepared liquid to the second prepared liquid, mixing evenly to obtain a third prepared liquid, stirring the third prepared liquid continuously for 8 minutes, and filtering with a 200-mesh filter cloth to obtain a membrane-forming liquid; The dispersant is selected from any one of alkyl sulfate, alkyl sulfonate, and sodium pyrophosphate; The magnesium alloy sheet is placed in a film-forming liquid for treatment; The treatment method of the magnesium alloy plate and the film-forming liquid is as follows: immerse the magnesium alloy plate in the film-forming liquid for 6 minutes, continuously stir the film-forming liquid during the immersion process, slowly take out the magnesium alloy plate, let it stand for 3 minutes and continue to immerse it in the film-forming liquid for 6 minutes, repeat the immersion and taking out and standing operation 6 times, hang the magnesium alloy plate in an oven set at 230°C, keep it warm for 20 minutes, take it out and place it at room temperature for 12 hours to complete the treatment.

[0050] Comparative Example 1: This comparative example differs from Experiment 1 in that it does not contain a covering material.

[0051] Comparative Example 2: The difference between this comparative example and Experiment 1 is that no film-forming liquid immersion treatment is performed.

[0052] Comparative Example 3: The difference between this comparative example and Experiment 1 is that no vanadyl sulfate is added when preparing the membrane-forming solution.

[0053] Comparative Example 4: This comparative example differs from Experiment 1 in that no soaking liquid treatment was performed.

[0054] Performance test: The performance test was carried out on the magnesium alloy plates after being treated in Experiment 1, Experiment 2, Experiment 3, Comparative Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4, and the obtained test data were recorded in the following table:

[0055] In the performance test, the corrosion resistance test method is as follows: weigh and record the magnesium alloy plates, prepare a sodium chloride solution with a concentration of 50g / L, adjust the temperature to 35°C, spray the surface of each magnesium alloy plate at a fixed spraying frequency and spraying amount, place it in the same environment for 12 hours after spraying, then sandblast the surface of each aluminum alloy plate to remove rust, and weigh and record after cleaning.

[0056] Among them, the masses of the aluminum alloy plates before the test were 503.4g, 500.8g, 501.8g, 505.6g, 503.8g, 500.4g and 502.7g respectively. After being sprayed with sodium chloride solution, the masses of the aluminum alloy plates were 498.6g, 496.2g, 496.6g, 493.4g, 496.3g, 494.3g and 497g respectively. The weight differences of the aluminum alloy plates before and after spraying were 4.8g, 4.6g, 5.2g, 12.2g, 7.5g, 6.1g and 5.7g respectively. The hardness test data of each aluminum alloy plate are 78, 81, 79, 47, 51, 56 and 61 respectively.

[0057] It can be seen that the corrosion resistance and hardness data of the aluminum alloy plates after treatment in Comparative Examples 1, 2, 3 and 4 are lower than those in Experiments 1, 2 and 3; this shows that: the passivation layer plays a role of corrosion protection on the surface of the magnesium alloy, and at the same time, the magnesium alloy plate is pre-treated by the immersion liquid and the covering material. After the magnesium alloy plate is subsequently heated, the carbohydrate in the immersion liquid is used as the main raw material, which can produce gelatinization when heated and produce cross-linking reaction with the magnesium alloy plate, the covering material and the film-forming liquid, which is used to optimize the surface pore structure of the plate, thereby optimizing the film-forming performance of the silane composite passivation layer. The passivation layer wraps the gelatinization layer formed by the immersion liquid inside, effectively improving the cross-linking density of silane in the passivation layer, thereby improving the density of the passivation layer, and then improving the corrosion resistance of the magnesium alloy. After being prepared into a slurry, the metal powder is evenly filled between the gelatinized carbohydrate water and the passivation layer, and hardened to form a solidified layer after drying and heating treatment, which plays a role in improving the surface hardness of the magnesium alloy plate.

[0058] By comparing and analyzing the relevant data in the table, it can be seen that the magnesium alloy treated by the method for improving the corrosion resistance of magnesium alloy of the present invention not only has good corrosion resistance, but also has excellent hardness performance. This shows that the method for improving the corrosion resistance of magnesium alloy provided by the present invention has a broader market prospect and is more suitable for promotion.

[0059] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0060] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A method for improving the corrosion resistance of a magnesium alloy, characterized in that: The following steps are involved: S1: Select a magnesium alloy plate, and use sandpaper to grind the surface of the magnesium alloy plate to remove burrs; S2: preparing a soaking liquid, and placing the magnesium alloy sheet into the soaking liquid for soaking; S3: preparing a covering material, and coating the surface of the magnesium alloy sheet with the covering material, sending the coated magnesium alloy sheet into an oven, and drying it at 220° C. to 240° C. for 3 h to 5 h; S4: performing micro-forging hammering treatment on the surface of the magnesium alloy plate; S5: preparing a film-forming liquid, and placing the magnesium alloy sheet after micro-forging and hammering into the film-forming liquid for treatment; The preparation of the film-forming liquid includes: S511. adding aminopropyl triethoxysilane to water, mixing and stirring for 10 to 15 minutes, and then adding ammonia water to adjust the pH value to 7 to obtain a first prepared liquid; S512. adding propyl trimethoxysilane to the first prepared liquid, heating to 80 to 90°C, keeping warm for 50 to 60 minutes, stirring slowly during the insulation process, adding vanadyl sulfate after cooling to room temperature, and then adding ammonia water to adjust the pH value to 6.5 to obtain a second prepared liquid; S513. adding a dispersant to the second prepared liquid, mixing evenly to obtain a third prepared liquid, stirring the third prepared liquid for 5 to 8 minutes, and filtering with a 200-mesh filter cloth to obtain a film-forming liquid; The magnesium alloy sheet is placed in the film-forming liquid for treatment, including: S521. Immersing the magnesium alloy sheet in the film-forming liquid for 4 to 6 minutes, and continuously stirring the film-forming liquid during the immersion process; S522. Slowly taking out the magnesium alloy sheet and letting it stand for 2 to 3 minutes; S523. Repeating S521 and S522 in sequence for 4 to 6 times; S6: Hang the magnesium alloy plate in an oven, keep it at 220° C. to 230° C. for 15 to 20 minutes, take it out and place it at room temperature for 12 hours to complete the treatment.

2. The method for improving the corrosion resistance of magnesium alloy according to claim 1, characterized in that: In the S511, when the aminopropyltriethoxysilane is added to the water, the mass ratio of the water to the aminopropyltriethoxysilane is 1:(0.1-0.2).

3. The method for improving the corrosion resistance of magnesium alloy according to claim 2, characterized in that: In the S512: When the propyltrimethoxysilane is added to the first formulation, the mass of the added propyltrimethoxysilane accounts for 25-30% of the mass of the first formulation; When the vanadyl sulfate is added to the first formulated liquid, the mass of the added vanadyl sulfate accounts for 10-15% of the mass of the first formulated liquid.

4. The method for improving the corrosion resistance of magnesium alloy according to claim 3, characterized in that: In the step S513, when the dispersant is added to the second prepared liquid, the mass of the added dispersant accounts for 4-6% of the mass of the second prepared liquid.

5. The method for improving the corrosion resistance of magnesium alloy according to claim 4, characterized in that: The dispersant is selected from any one of alkyl sulfate, alkyl sulfonate and sodium pyrophosphate.

6. The method for improving the corrosion resistance of magnesium alloy according to claim 5, characterized in that: In S2, preparing the soaking liquid includes: adding corn starch into water in a mass ratio of 1: (3-4), stirring and mixing for standby use, and continuing to stir evenly during use and soaking.

7. The method for improving the corrosion resistance of magnesium alloy according to claim 6, characterized in that: In S3, the preparation of the covering material includes: S31. Weigh 10 to 12 parts of ferric oxide powder, 8 to 10 parts of nickel oxide powder, 6 to 8 parts of calcium fluoride powder and 4 to 6 parts of silicon dioxide powder, all of which are put into a mixer to obtain a mixture; S32. Adding a mixed liquid having a mass of 1.4 to 1.6 times the mass of the mixed material to the mixed material, and obtaining a slurry after mixing; S33. The slurry is fed into a magnetic stirrer and stirred at a speed of 600 to 800 r / min for 40 to 50 min to obtain a covering material.

8. The method for improving the corrosion resistance of magnesium alloy according to claim 7, characterized in that: In the S31, the particle sizes of the ferric oxide powder, the nickel oxide powder, the calcium fluoride powder and the silicon dioxide powder are all less than or equal to 20 μm.

9. The method for improving the corrosion resistance of magnesium alloy according to claim 8, characterized in that: Before adding the mixed liquid having a mass 1.4 to 1.6 times the mass of the mixed material into the mixed material in S32, the method further comprises: The mixed solution is prepared by mixing glycerol and anhydrous ethanol in a mass ratio of 1:(0.4-0.6).

10. The method for improving the corrosion resistance of magnesium alloy according to claim 9, characterized in that: In S4, performing micro-forging hammering treatment on the surface of the magnesium alloy plate comprises: Placing the magnesium alloy plate on a hammering device; The micro-forging head of the hammering device has a diameter of 3 to 5 mm, a stroke of 1.5 to 2 mm, an impact frequency of 100 Hz, a step size of 0.1 mm, and a feed speed of 600 to 800 mm / min; The micro-forging head is controlled to hammer the magnesium alloy plate.

Citation Information

Patent Citations

  • Method for forming silane film on surface of magnesium alloy

    CN102453892A

  • Preparation method of in-situ synthesized self-repairing magnesium alloy corrosion-resistant coating

    CN110938814A

  • Vacuum melting and vacuum ingot casting device and process for clean magnesium metal and alloy thereof

    CN112207240A

  • Corrosion-resistant magnesium alloy material as well as preparation method and application thereof

    CN118389021A

  • Coating solution for magnesium materials having excellent corrosion resistance, method of preparing the same, and coating method of magnesium materials using the same

    KR1020120099169A